Exploring EFL Students' Perceptions of Utilizing Harry Potter Movies for English Idiom Acquisition - iga wahyuni (PT MEDIA JURNAL DAN PENDIDIKAN, 2025)
Mastering English idioms presents a significant challenge for English as a Foreign Language (EFL) learners due to their non-literal meanings. Integrating audiovisual media, such as movies, is theorized to provide the necessary contextual scaffolding. This research aimed to investigate the implementation of the Harry Potter movie series in teaching idioms and to explore students' perceptions of this media at Universitas Pohuwato. Employing a descriptive qualitative method supported by quantitative survey data, the study involved fourth-semester students from the English Education Department. Data were collected through questionnaires distributed to nine students and in-depth interviews with a purposive sample of six students. The synthesized results indicate a highly positive perception; 100% of respondents strongly agreed on the importance of learning idioms, and the majority found the movie engaging and effective for vocabulary expansion. Although students faced difficulties comprehending the British accent and rapid speech, the visual context of the movie significantly aided their idiomatic comprehension. In conclusion, utilizing Harry Potter movies is an effective pedagogical strategy that boosts student motivation and enriches their idiomatic repertoire, provided that lecturers offer adequate linguistic guidance.